Microwave enhanced alcoholysis of non-edible (algal, jatropha and pongamia) oils using chemically activated egg shell derived CaO as heterogeneous catalyst. (November 2016) - Joshi, Girdhar; Rawat, Devendra S.; Sharma, Amit Kumar; Pandey, Jitendra K.
Highlights: Microwave enhanced alcoholysis of algal, jatropha and pongamia oils were achieved. Chemically activated waste egg shell derived CaO was used as heterogeneous catalyst. Effect of aliphatic chain of alcohol on biodiesel yields was observed. ZnO-CaO(cesp) was found the best among all. ZnO-CaO(cesp) has shown good reusability up to 4 cycles without significant loss of catalytic activity. Abstract: Microwave enhanced fast and efficient alcoholysis (methanolysis and ethanolysis) of non-edible oils ( algal, jatropha and pongamia ) is achieved using chemically activated waste egg shell derived CaO ( i.e. CaO(cesp)) as heterogeneous catalyst. CaO(cesp) was extracted from waste chicken egg shell and further activated chemically by supporting transition metal oxide. The maximum conversion was achieved using 3 wt% catalysts under 700 W microwave irradiation and 10:1 alcohol/oil ratio in 6 min. Alcoholysis using ZnO activated CaO(cesp) catalyst has shown higher reaction yields in comparison to other modified catalysts. Methanolysis has shown better biodiesel conversion in comparison to ethanolysis. The catalyst has shown longer lifetime and sustained activity after being used for four cycles. Due to more saturated fatty acid content; algal biodiesel has shown improved fuel properties in comparison to other biodiesels.